The Influence of Entrepreneurship Education and Locus of Control on Entrepreneurial Intention with Entrepreneurial Motivation as a Moderating Variable - Herlyna Talia; Mochamad Soelton (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to evaluate the effect of Entrepreneurship Education and Locus of Control on Entrepreneurial Intention by considering the role of Entrepreneurial Motivation as a moderating variable. The object of this research is Regular Management 1 students of Universitas Mercu Buana class of 2021-2023. The approach used is quantitative with purposive sampling method, involving 155 respondents. Data collection was carried out through distributing questionnaires online and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 4.0 software. The results of the analysis show that: (1) Entrepreneurship Education has a positive and significant effect on Entrepreneurial Intention; (2) Locus of Control also shows a positive and significant effect on Entrepreneurial Intention; (3) Entrepreneurial Motivation does not act as a moderator in the relationship between Entrepreneurship Education and Entrepreneurial Intention; and (4) Entrepreneurial Motivation is not able to moderate the relationship between Locus of Control and Entrepreneurial Intention.